La valoración del testimonio anticipado de la víctima de delitos sexuales, frente al principio de duda razonable. - Carrasco Chauca, Jomayra Baltazara (2026)
This study examines the evaluation of advance testimony from victims of sexual crimes considering the principle of reasonable doubt, aiming to identify the criteria judges apply to issue fair sentences. It explores whether the rights and guarantees of the accused are compromised during the admission of such testimony. Using a legal-dogmatic approach combined with case analysis, the research reviews national and international jurisprudence to uncover inconsistencies in the assessment of advance testimony that disregard reasonable doubt. The findings reveal deficiencies in prosecutorial investigations, particularly in the search for both incriminating and exculpatory evidence, which often results in undue reliance on advance testimony as primary proof. Interviews with judges and surveys of criminal law professionals further expose shortcomings in its evaluation, including cases where this testimony has been treated as sole evidence without reliable mechanisms to verify its truthfulness. The study concludes that advance testimony should not outweigh other evidence but must be assessed comprehensively and accompanied by cross-examination at the time it is taken. In an oral adversarial system, both parties must operate on equal footing; thus, the ultimate goal should be to establish the truth and avoid convicting an innocent person when doubts persist, particularly regarding testimony susceptible to external influences.